Implementasi Pembelajaran Gamelan Sebagai Sarana Penguatan Karakter Siswa Di Sekolah Dasar - Klara Natalia; Cicilia Ika Rahayu Nita; Andika Gutama (CV. Multi Kreasi Media, 2025)
This study focuses on the implementation of Gamelan learning as a medium for instilling character values in students at SDN Sukun 1 Malang. Character education is an important aspect of learning in elementary schools, aimed at shaping the personality, morals, and ethics of students. One way to apply character education is through traditional Gamelan art learning. Gamelan art not only plays a role in cultural preservation but also serves as an effective means of teaching values such as discipline, responsibility, cooperation, and perseverance. The problem addressed in this research is the lack of integration of character education in elementary school learning, necessitating an effective method through Gamelan learning to instill character values in students. This study uses a qualitative approach with a descriptive method. Data collection was conducted through observation, interviews with teachers and students, and documentation of the Gamelan learning process. Data analysis was performed interactively with stages of data reduction, data presentation, and conclusion drawing. The findings of the research indicate that Gamelan learning has a positive impact on the formation of student character. Through regular Gamelan practice, students become more disciplined in participating in activities, demonstrate responsibility for the musical instruments used, and are able to cooperate in creating musical harmony. Additionally, Gamelan learning also enhances students' self-confidence and love for local culture. This learning not only functions as a means of cultural preservation but also helps shape students' personalities holistically.